Phage-based detection of Escherichia coli O157:H7 in leafy greens (2025)
Escherichia coli O157:H7, due to its low infectious dose and severe symptoms such as hemolytic uremic syndrome, is particularly dangerous. Detecting pathogens in foods like lettuce, a common vehicle for contamination, requires a faster and more sensitive method than conventional techniques. This project proposes a detection method based on bioluminescence using a modified phage specific for E. coli O157:H7, фV10, by inserting the luxCDABE operon and the kanamycin resistance gene. The infection and genome insertion of фV10lux into O157:H7 generate luciferase and its substrate through the complete luxCDABE operon, producing light proportional to the number of viable E. coli cells. The kanamycin gene allows the selection of successfully modified cells. Concentration techniques and food-related conditions were applied to evaluate phage performance, determining the minimum number of bacteria required to produce detectable light and the minimum amount of phage necessary to ensure E. coli detection. Laboratory assays are expected to achieve detection limits below 10^3 CFU/ml for bacterial cells and 10^5 CFU/ml for phage particles. Various temperatures, concentrations, and incubation times were assessed before adding kanamycin, with no significant differences expected in bioluminescence detection. In food matrices such as parsley and cilantro, detection was anticipated to be comparable to laboratory conditions. This method aims to be easily implemented at critical points in the food supply chain to improve pathogen detection and food safety.